Self-enforcing environmental agreements and trade in fossil energy deposits - Thomas Eichner; Rüdiger Pethig (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 2015)
This paper analyzes the formation of self-enforcing climate agreements, or stable climate coalitions, when all countries have the option to fight climate change by purchasing (the right to extract) fossil-energy deposits. First, we consider the stand-alone deposit purchase policy and then combine that policy with the option to tax or subsidize the supply of deposits. In either case, coalitions of any size turn out to buy deposits while the non-cooperative countries do not. In case of the standalone deposit purchase policy either no coalition is stable or the grand coalition is the only stable coalition. If the two-instrument policy is implemented, all countries inside and outside the coalition are better off than in case of the stand-alone deposit policy, but the conditions for stable grand coalitions are more favorable under the stand-alone deposit policy than under the two-instrument policy due to weaker free-rider incentives.
Keywords: C72; Q38; Q58; 330; climate coalition; deposit; fuel; Nash; self-enforcing IEA